Women, Water and the Marsh: Adaptation Pathways of Agusan Marsh Indigenous Communities in Mindanao, Southern Philippines - Tomas, Rosalinda C. (JPAIR Multidisciplinary Research, 2009)
Seasonal fluctuation of the quantity and the quality as well as access to potable water are critical factors affecting livelihoods, health and over well-being of the 117,683 peoples depending on the viability of the Agusan Marsh in Southern Philippines. With no immediate facilities and mechanism to seek for cleaner water, the Agusan Marsh communities are at stake as they become prone to shifting climatic regimes and changing socio-economic and ecological situations in the marsh. The study was undertaken to explore what measures the communities need to undertake to reduce their vulnerabilities and increase their capacities in the face of changing climate regimes. Focus was on the adaptive pathways of the Agusan marsh communities, with particular interest on women’s contribution in health and natural resource management. In the face of critical water needs in the marshlands, (1) developing appropriate infrastructures for resource provisioning that can withstand the seasonal fluctuations and changing climate regimes in the region, and (2) developing a garbage disposal or sanitation system that is appropriate for perennially flooded or permanently floating communities emerge as two of the most important long-term adaptive strategies of the communities.